Psychological disorders and the performance some cognitive processes in a migraine patient -Case Study - Demdoum, Rima; Nassima (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The migraine headache is treated as an unpleasant sensory experience, which results in a change in the psychological state, and the latter may also be an alarming factor for headache. Migraine goes beyond the cognitive state of the individual, social and professional status, it makes individuals unable to perform their daily tasks. Hence, this study came with the aim of detecting mental disorders that a migraine patient suffers from and also to reveal the performance of some cognitive processes that it has, and to achieve the objectives of the study, the clinical approach that is based on the case study was followed, and a set of tools were used: the semi-directed interview. Moreover, the Arabic version of MMPI-2 was used from Abdullah Mahmoud Suleiman's translation and the Addenbrooke’s Cognitive Examination – Revised (ACE-R) translated by Al Salman (2013). The results of the study are as follow : - An increase in several clinical measures of MMPI2 : Paranoia, hysteria, schizophrenia, Hypocondrie, depression, psychopathic deviation. - The presence of an increase in some additional measures, namely: post-traumatic stress disorder and academic maladjustment - There was an increase in some content measures, represented in : family problems, health concerns, anger, social discomfort, fear and strange thoughts - The psychological page showed psychotic tendencies - Decreased cognitive status in the case and a decrease in the performance of some cognitive processes represented in : attention, memory and language, which deteriorate during a headache. The study recommended that treatment programs should be designed to alleviate the psychological and cognitive suffering of migraine patiente.